2001
DOI: 10.1016/s0002-9440(10)64127-2
|View full text |Cite
|
Sign up to set email alerts
|

Human Trophoblast Invasion and Spiral Artery Transformation

Abstract: During early human pregnancy extravillous cytotrophoblasts invade the uterus and spiral arteries transforming them into large vessels of low resistance. Failure of trophoblast invasion and spiral artery transformation occurs in preeclampsia and fetal growth restriction (FGR); these processes are not well understood. Recent studies have suggested that cytotrophoblasts that invade spiral arteries mimic the endothelial cells they replace and express PECAM-1. It was also reported that in preeclampsia, cytotrophobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(42 citation statements)
references
References 59 publications
0
37
0
1
Order By: Relevance
“…While the precise mechanisms involved in uterine spiral artery remodeling have yet to be established, interstitial and perivascular EVT have been implicated. EVT migrate into the maternal decidua and myometrium from 12–16 weeks of gestation in association with vascular remodeling [28]. Furthermore, it has been proposed that inadequate invasion of EVT into the myometrium is associated with a failure to remodel uterine spiral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…While the precise mechanisms involved in uterine spiral artery remodeling have yet to be established, interstitial and perivascular EVT have been implicated. EVT migrate into the maternal decidua and myometrium from 12–16 weeks of gestation in association with vascular remodeling [28]. Furthermore, it has been proposed that inadequate invasion of EVT into the myometrium is associated with a failure to remodel uterine spiral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced uteroplacental perfusion in preeclamptic pregnancies is associated with endothelial dysfunction, which is one of the causes leading to the failures of trophoblast invasion and spiral artery transformation, and which results in an impaired placentation [8]. In preeclamptic pregnancies there are no inadequate physiologic changes of spiral arteries remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that an important factor for proper trophoblast invasion and vascular remodelling is the expression and activity of adhesion molecules [8,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…These changes, that include gradual loss of the musculoelastic structure of the arterial wall and replacement by amorphous fibrinoid material, are essential to create vessels of low resistance unresponsive to vasoconstrictive agents [1, 2] allowing continuous blood flow in the intervillous space. …”
Section: Introductionmentioning
confidence: 99%